Novel findings and expansion of phenotype in a mosaic RASopathy caused by somatic KRAS variants. Issue 9 (30th May 2021) - Chang, Caitlin A.; Perrier, Renee; Kurek, Kyle C.; Estrada‐Veras, Juvianee; Lehman, Anna; Yip, Stephen; Hendson, Glenda; Diamond, Carol; Pinchot, Jason W.; Tran, Jennifer M.; Arkin, Lisa M.; Drolet, Beth A.; et al.
Abstract: Mosaic KRAS variants and other RASopathy genes cause oculoectodermal, encephalo‐cranio‐cutaneous lipomatosis, and Schimmelpenning‐Feuerstein‐Mims syndromes, and a spectrum of vascular malformations, overgrowth and other associated anomalies, the latter of which are only recently being characterized. We describe eight individuals in total (six unreported cases and two previously reported cases) with somatic KRAS variants and variably associated features. Given the findings of somatic overgrowth (in seven individuals) and vascular or lymphatic malformations (in eight individuals), we suggest mosaic RASopathies (mosaic KRAS variants) be considered in the differential diagnosis for individuals presenting with asymmetric overgrowth and lymphatic or vascular anomalies. We expand the association with embryonal tumors, including the third report of embryonal rhabdomyosarcoma, as well as novel findings of Wilms tumor and nephroblastomatosis in two individuals. Rare or novel findings in our series include the presence of epilepsy, polycystic kidneys, and T‐cell deficiency in one individual, and multifocal lytic bone lesions in two individuals. Finally, we describe the first use of targeted therapy with a MEK inhibitor for an individual with a mosaic KRAS variant. The purposes of this report are to expand the phenotypic spectrum of mosaic KRAS ‐related disorders, and to propose possible mechanisms of pathogenesis, and surveillance of its associated findings.